2022
DOI: 10.3389/fphys.2022.839217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Ramie Powder (Boehmeria nivea) at Various Levels on Growth Performance, Carcass and Meat Qualities, Biochemical Indices, and Antioxidative Capacity of Linwu Ducks

Abstract: Current experiment was designed to check the effect of dietary supplementation of ramie powder on the growth performance, carcass and meat qualities and antioxidative capacity of Linwu ducks. A total of 312 ducks at 21-day-age were equally divided into 4 groups, fed with control diet, control diet supplemented of 3, 6, or 12% ramie powder, respectively. The results showed that dietary supplementation of 6 and 12% ramie powder increased the final weight and daily body weight gain (P < 0.05), and dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Li et al found that diets supplemented with 9% and 12% ramie reduced the final body weight and ADG in finishing pigs compared to the control diets, but the ADFI did not change [ 10 ]. However, Lin et al pointed out that the addition of 6% and 12% ramie to the diet can significantly increase the final body weight and ADG of Linwu ducks, but the addition of ramie had no effect on the ADFI [ 11 ]. Similarly, the present study showed that dietary supplementation of 12% ramie significantly increased the final body weight of Yanling white geese compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al found that diets supplemented with 9% and 12% ramie reduced the final body weight and ADG in finishing pigs compared to the control diets, but the ADFI did not change [ 10 ]. However, Lin et al pointed out that the addition of 6% and 12% ramie to the diet can significantly increase the final body weight and ADG of Linwu ducks, but the addition of ramie had no effect on the ADFI [ 11 ]. Similarly, the present study showed that dietary supplementation of 12% ramie significantly increased the final body weight of Yanling white geese compared to the control group.…”
Section: Discussionmentioning
confidence: 99%